DEVELOPMENT OF INQUIRY-BASED DIGITAL WORKSHEET TO IMPROVE MATHEMATICAL THINKING ABILITY - Chamila Putri Audina; Ely Susanti; Nyimas Aisyah (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2025)
One of the mathematical abilities that schools are expected to develop is students’ mathematical thinking ability. However, many students still struggle in this area due to the use of learning methods that are not aligned with students’ characteristics and learning environments. These methods often lack opportunities for student interaction and fail to accommodate individual learning levels, resulting in limited engagement and development of higher-order thinking. This condition indicates the need for innovative learning approaches that promote active involvement, interaction, and reasoning. Inquiry-based learning, supported by digital worksheets, is one such approach that can help improve students’ mathematical thinking. This research aims to develop valid and practical inquiry-based digital worksheets on the topic of cubes and beams for grade 8 students and to examine their potential to enhance students’ mathematical thinking ability. The study consists of two stages: the preliminary stage, which involves the development of the worksheet concept and design, and the prototyping stage, which includes self-evaluation, expert review, one-to-one, small group, and field testing. Validity data obtained from expert reviews show an average score of 87%, categorized as very valid, while practicality data yield an average score of 79%, categorized as practical. The students’ work on the tasks indicates a high level of mathematical thinking, with 79.3% of students categorized as very good, 10.3% as good, 3.4% as sufficient, and 6.9% as less. Interview results based on mathematical thinking indicators show that the most frequently demonstrated indicator is specialization, while conjecture appears the least. These findings suggest that inquiry-based digital worksheets have the potential to support the development of students’ mathematical thinking.